2013
DOI: 10.4103/0973-029x.125203
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and correlative study of salivary nitrate and nitrite in tobacco related oral squamous carcinoma and submucous fibrosis

Abstract: Oral cancer is one of the ten leading cancers of the world. In India, it is one of the common cancers and is an important public health problem. Tobacco plays significant role in etiology of oral squamous carcinoma. Tobacco which is chewed or smoked contains many alkaloids which are known carcinogens. Oral submucous fibrosis (OSMF) is a disease of the Indian subcontinent, which through immigration has a worldwide distribution. Betel nut chewing plays significant role in etiology of OSMF. The nut alkaloids have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This hypothesis was validated, as we demonstrated that repeated exposure to CS led to a decrease in Bax expression and to an increase in Bcl‐2 expression. The increased cell proliferation and apoptosis resistance may thus explain how CS promotes oral pathologies, such as periodontal disease, and even cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis was validated, as we demonstrated that repeated exposure to CS led to a decrease in Bax expression and to an increase in Bcl‐2 expression. The increased cell proliferation and apoptosis resistance may thus explain how CS promotes oral pathologies, such as periodontal disease, and even cancer development and progression .…”
Section: Discussionmentioning
confidence: 99%
“…Although our 3D sl-µPADs needed the longer time for reaction (15 min) and the bigger volume for sample introduction (18 µL) than some work shown in Table 1 , the linear ranges and the LODs obtained in this work were comparable with those given by other sensors. Therefore, the fabricated 3D sl-µPADs provided an analytical platform to quantitatively detect nitrite and thiocyanate at the levels normally found in saliva [ 45 , 46 , 47 ]. Moreover, a heating step was added to study the possibility of the shorter testing time.…”
Section: Resultsmentioning
confidence: 99%
“…For example, leafy green spinach has a basic pH and is highly rich in nitrate [ 167 ]. The high content of nitrate increases nitrite concentrations in saliva [ 106 ], which in turn could lead to toxic nitrosation of arecoline [ 168 ]. Thus, it is unlikely that spinach consumption would protect against the toxic effects of arecoline.…”
Section: Potential Dietary Measures To Reduce Adverse Effects Of mentioning
confidence: 99%